Personal ornaments from Hayonim and Manot caves (Israel) hint at symbolic ties between the Levantine and the European Aurignacian. Issue 160 (November 2021) - Tejero, José-Miguel; Rabinovich, Rivka; Yeshurun, Reuven; Abulafia, Talia; Bar-Yosef, Ofer; Barzilai, Omry; Goder-Goldberger, Mae; Hershkovitz, Israel; Lavi, Ron; Shemer, Maayan; Marder, Ofer; Belfer-Cohen, Anna
Abstract: Situated at the crossroads of Africa and Eurasia, the Levant is a crucial region for understanding the origins and spread of Upper Paleolithic (UP) traditions associated with the spread of modern humans. Of the two local Early Upper Paleolithic technocomplexes, the Ahmarian and the Levantine Aurignacian, the latter appears to be unique in the endemic UP sequence, exhibiting greater similarity to the West European 'classic' Aurignacian than to the local preceding and proceeding UP entities. Previous publications have mostly focused on the similarities between the two lithic industries and less on studies conducted on Levantine Aurignacian bone tools and ornaments. Here, we present an archaeozoological, technological and use-wear study of ornaments on animal teeth from the Levantine Aurignacian layers at Manot and Hayonim caves (the Galilee, Israel). The selection of taxa, the choice of teeth, the mode of modification, and the use-wear analysis exhibit clear similarities with the European Aurignacian. This, with the technology of the osseous raw material exploitation, the presence of antler simple-base points, and some lithic typotechnological features, suggest a link between the symbolic spheres of the Levantine and the European Aurignacian cultural entities. Such similarity also supports some contribution of European Aurignacians groups to the local cultural entities, intermingling with the local material culture features.